INTRODUCING COOPERATIVE LEARNING IN THE ENGLISH LANGUAGE CLASSROOM AND PROGRESS TRACKING: (AT THE DEPARTMENT OF TRANSLATION AND INTERPRETING IN SKOPJE) (Journal of Contemporary Philology, 2021)
The English language classroom has been experiencing a shift from the traditional approach towards a functional approach to teaching. The purpose is to abandon the classical lecture-and-note approach, passive role of students, an unproductive classroom and excessive teacher-reliance, thereby putting emphasis on interaction and collaboration in the English language classroom as well as on student autonomy in the learning process. The aim of this paper is to analyse efficient methods for teaching grammar and to explore which learning practices are deemed best by students. For the purposes of this research, a survey was conducted among 50 first-year students at the Faculty of Philology (whose progress in learning grammar was monitored in a period of two semesters). The results of the research indicate a need for applying an action-based approach in the English language classroom, whereas the authors suggest different cooperative learning strategies. Furthermore, the results demonstrate that teaching methods have an effect on the level of progress achieved by students, whereas the need for introducing progress tracking at faculty level is also discussed.
Keywords: cooperative teaching; learning strategies; EFL; progress tracking